Analisis Disain 25 Step Mosfet Multilevel Inverter Terkendali SPWM - setiyono, Setiyono setiyono (ENERGI & KELISTRIKAN, 2024)
This paper presents a 25 level DC to AC voltage converter technique using a MOSFET with Sinusoidal Pulse Width Modulation (SPWM) control. The goal is to make an inverter that has an output voltage close to a sinusoid with the lowest possible harmonic content. The method used is to build a single-pole ladder type cascade multilevel inverter using a MOSFET semiconductor device equipped with a snubber protector when under inductive load through modeling simulations with Matlab Simulink. The simulation results show the inverter output voltage waveform in the form of a ladder wave of 25 amplitude levels 220 V with a frequency of 50 Hz with a THD of 10.26%. This design is expected to be a reference for researchers for further research and can be implemented into an electronic circuit.